1984
DOI: 10.1080/00039896.1984.10545830
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Symptoms in Patients with Chronic Obstructive Pulmonary Disease and in Other Subjects Living near a Coal-Fired Plant

Abstract: Daily symptom rates in patients with chronic obstructive pulmonary disease and in other subjects with presumed high sensitivity to air pollution who lived near a coal-fired plant were compared with 24-hr ambient air concentrations of nitrogen dioxide, sulfur dioxide, soot, and suspended particles as well as with emissions from the plant. The mean concentrations of each of the pollutants during the 4-month study period were below 30 micrograms/m3, and no single 24-hr concentration exceeded 100 micrograms/m3. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the 1960s, panel studies in COPD and asthma patients were also carried out in Chicago and Baltimore, showing associations between (lagged) air pollution levels and respiratory symptoms (Burrows et al, 1968;Carnow et al, 1969) and lung function (Spicer et al, 1966). In the early 1980s, a panel study was performed among subjects living near a coal-fired power plant in Finland, including 43 hospital patients with COPD (Pershagen et al, 1984). On days with high ambient soot levels, an increase in respiratory symptoms was observed in these patients, but the pollution levels could not be linked to the plant emissions.…”
Section: Early Panel Studiesmentioning
confidence: 99%
“…In the 1960s, panel studies in COPD and asthma patients were also carried out in Chicago and Baltimore, showing associations between (lagged) air pollution levels and respiratory symptoms (Burrows et al, 1968;Carnow et al, 1969) and lung function (Spicer et al, 1966). In the early 1980s, a panel study was performed among subjects living near a coal-fired power plant in Finland, including 43 hospital patients with COPD (Pershagen et al, 1984). On days with high ambient soot levels, an increase in respiratory symptoms was observed in these patients, but the pollution levels could not be linked to the plant emissions.…”
Section: Early Panel Studiesmentioning
confidence: 99%
“…In addition, an intensified study was made in one of the areas of subjects believed to be sensitive to air pollution. This study has been reported elsewhere (10).…”
Section: Introductionmentioning
confidence: 61%
“…This indicates that the coal-fired plants had no major influence on the occurrence of these health effects in the surrounding population. The mean concentrations of SO2, NO2, soot, and suspended particulates in ambient air during 1981-82 in area D and in its reference area were similar and low, i.e., below 30 ,ug/m3 (10). In area B and its reference area, yearly SO2 concentrations in 1977 were estimated to be 25 to 35 ,ug/m3 (11).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the coal-fired plants had no major influence on the occurrence of these health effects in the surrounding population. The mean concentrations of SO2, NO2, soot, and suspended particulates in ambient air during 1981-82 in area D and in its reference area were similar and low, i.e., below 30 ,ug/m3 (10). In area B and its reference area, yearly SO2 concentrations in 1977 were estimated to be 25 to 35 ,ug/m3 (11).…”
Section: Discussionmentioning
confidence: 87%